The prediction for risk of food allergy in children with chronic Helicobacter pylori associated infection - A.E. Lykova (Zaslavsky O.Yu., 2019)
Background. Etiology and pathogenesis of food allergy in children is not completely known to the present day. The role of a number of factors, including chronic Helicobacter pylori associated infection, has been described. The purpose of the study was to identify informatively significant biomedical and socio-hygienic risk factors for the development of allergy in children with chronic Helicobacter pylori associated infection, as well as to create a mathematical model to forecast the probability of the presence or development of an allergic pathology. Materials and methods. We've examined 76 children aged 7 to 17 years with chronic Helicobacter pylori associated infection, who were examined and treated in the Gastroenterological Department of Dnipropetrovsk Municipal Clinical Hospital 1. Results. The risk factors were identified and a mathematical model for forecasting the development of food allergy in children with chronic Helicobacter pylori associated infection was developed. The following factors have prognostic value as the duration of the disease over 32 months, the duration of the pain syndrome over 7 days, the higher education in a child's parent. The following endoscopic manifestations also have a significant impact: erosive focal gastritis, erosive focal bulb, ulcer on the anterior wall of the duodenum, and superficial focal duodenitis. Conclusions. The results showed that the presence of chronic Helicobacter pylori associated infection provokes the development of food allergies in children. The mathematical model of forecasting can be used in the practice of family doctors, pediatricians and pediatric gastroenterologists.